Analisa Pengaruh Pandemi Covid-19 terhadap Kinerja Keuangan Sektoral Perusahaan Emiten di Bursa Efek Indonesia - Budi Santoso (Journal of Management and Business Review, 2021)
Covid-19, which has become a worldwide pandemik, has had an impact on various sectors ranging from healthcare, social, economic, education and several other sectors. The first Covid-19 cases in Indonesia were detected in early March 2020, and up to October 18, 2020 there has been no decline in the trending number of cases, with the number of confirmed cases of 361,867 and active cases of 64,032. This condition has many impacts, one of which is the economic sector, especially the company's financial performance. This paper analyzes the effect of covid-19 on the financial performance of companies listed on the Indonesia Stock Exchange that are engaged in several business sectors. In each sector several sampels will be taken and analyzed several key indicators of the financial statements from the aspects of revenue, profit and liquidity ratio, and compare them with several time periods up to the third quarter of 2020. With this analysis, it can be taken into consideration for stakeholders to provide stimulation in order to accelerate economic recovery after Covid-19.